Island in the neoliberal stream: energy security and soft re-nationalisation in Hungary. Issue 1 (2nd January 2017) - Isaacs, Rico; Molnar, Adam
Abstract: Since 2010, the Hungarian Government has increased its stake in the country's energy sector at the expense of foreign-owned energy companies. This 'soft re-nationalisation' is driven by both exogenous and endogenous factors, especially the country's external dependence on gas imports, its previous commitment to a European model of energy liberalisation, public dissatisfaction with high energy prices and the emergence of an 'illiberal state'. The case of Hungary's 'soft re-nationalisation' yields two central findings. Firstly, conceptually, there is a need to move away from just focusing on the radical re-nationalisation of energy in the form of resource nationalism, and instead understand re-nationalisation as consisting of a broad spectrum of state interventions into the energy market. Secondly, Hungary's recent 'statist turn' in the energy sector highlights inherent tensions within EU energy policy as it threatens attempts to establish a fully liberalised and marketised energy market across the continent.